PROJECT DEVELOPMENT IN SMALL AND MEDIUM-SIZED ENTERPRISES: AN OPPORTUNITY TO IMPROVE TEACHING AND UNIVERSITY-BUSINESS INTERACTION - Rodrigues, José de Souza; Dalpian, Aline Martins Schneiders; Zambon, Kátia Lívia; Crepaldi, Antonio Fernando; Azzolini Júnior, Walther (Revista Gestão da Produção Operações e Sistemas, 2020)
Purpose: Assess whether project development in Small and Medium-sized Enterprises that supports the teaching-learning process (PBL methodology - Project Based Learning) is a solution to overcome the challenges of training professionals in the 21st century. Theoretical framework: Project development allows the student to be active in the teaching-learning process and enables technical and behavioral skills to be developed. Studies with SMEs are needed since it has not been researched greatly. Design/methodology/approach: Applied Research and the methodological approach were used for the case study. Projects were developed in two small enterprises and data was collected on students’ opinions regarding the process, where participant observation, documentation and interviews were used. Data was obtained in the period 2016 and 2017 in the region of Bauru-SP, Brazil, in partnership with SEBRAE (Brazilian Micro and Small Enterprise Support Service). Findings: The methodology based on project development in small enterprises motivates students and develops transferable skills which generates benefits for companies. Research, Practical & Social implications: Small enterprises provide the opportunity to look at companies as a whole and interact with all their employees, bringing the university closer to the community. Originality/value: small businesses can contribute to improving education by allowing collaborative university-company projects to develop. Keywords: PBL, small and medium-sized enterprises, engineering education, production systems